A study of assorted data on suicide bombings in Pakistan. (July 2019) - Rasheed, Sana; Khalid, Noman
Suicide terrorism is one of the most dreadful challenges for Pakistan as the country has been the primary and most frequent target of suicide terrorism in the world during recent years. Pakistan had two major sources of data on suicide bombings and related terrorism activities, the Pakistan Institute of Peace Studies and the Pakistan Body Count; however, these sources lacked comprehensive databases on these incidents and related news. The most reliable sources of information have been international data providers such as the Chicago Project on Security and Terrorism, the Global Terrorism Database Portal, and others. Recently, the Pakistan Body Count launched an improved version of its database with several new variables, updated information records, and error corrections. This study analyzes the datasets available from international organizations, the Pakistan Institute of Peace Studies, and the Pakistan Body Count and the variables recorded in them. It explains the benefits of the Pakistan Body Count data over other similar efforts, elaborates on the data collection methodology, provides a glimpse of possible analytics that can be performed using the updated dataset, and identifies areas of further improvement for this database.